TEACHER EDUCATION IN SPECIAL EDUCATION IN THE DISTANCE LEARNING MODALITY: EVALUATION OF A SPECIALIZATION AT A FEDERAL UNIVERSITY (Interdisciplinary Studies Journal, 2025)
The article analyzes the participants’ perceptions regarding the quality and relevance of a specialization course in Special and Inclusive Education offered in the distance-learning modality by a federal university, in partnership with the Open University of Brazil (UAB) system. The research, employing a qualitative approach with descriptive and exploratory characteristics, involved 110 participants and considered multiple dimensions of the training: curricular structure, content, teaching materials, institutional support, and the adequacy of the distance-learning format. Data were collected through an online questionnaire.The results reveal positive evaluations regarding the relevance of the content, the organization of the course, and the support provided by tutors and the coordination team. However, challenges were identified, such as coordination overload and limitations in administrative support.It is concluded that the training offered significantly contributes to the improvement of inclusive teaching practices, while highlighting the need for institutional strengthening to ensure equity and quality in future offerings. The study broadens the debate on teachers’ continuing education and points to paths for more effective public policies in promoting inclusive education through distance learning.
Keywords: Teacher Education; Open University of Brazil; Distance Education